Programming for Immigrant Women in Canada: Is Entrepreneurship Neglected?. (15th May 2020) - Kalu, Kenneth; Okafor, Oliver Nnamdi
Abstract: This study examines the demand and supply dynamics of entrepreneurship support services for new immigrant women in the Toronto Census Metropolitan Area (CMA), Ontario, Canada. Empirical evidence presented in this study reveals significant unmet needs for entrepreneurship support services. Major reasons for the inability of settlement agencies to meet the entrepreneurship needs of new immigrants include prioritization of other support services and lack of funding. The study identifies unfamiliarity with the Canadian environment, discrimination, business regulations that are difficult to satisfy, and unlikely tendencies of the immigrants to ask for support as some of the key challenges to entrepreneurship among immigrant women. However, these challenges may be ameliorated with enhanced entrepreneurship and language training, information awareness campaigns and more funding, among other factors. The findings have practical implications for accountable governments and non‐governmental organizations as they design and/or redesign immigration and settlement policies to facilitate integration of new immigrants.